I was so mad - Mayer, Mercer (Racine, WI : Western, 1983)
Little Critter feels so frustrated that he thinks of running away.
1.0
K-3
430L
J
Center for the Collaborative Classroom Curriculum.
Keywords: Runaways -- Fiction; Anger -- Fiction